Digitalisasi Dakwah Nahdlatul Ulama untuk Memaksimalkan Jangkauan Dakwah Islam Ahlusunah Wal Jama’ah di OKU Timur - Ahmad Sodikin; Sholeh Hasan; M Iqbal Musthafa; Umi Hanifah (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
The goal of PKM is to help partners solve their priority issues, including in the fields of digitization, account management, and the enhanced ability to read yellow book references to find material. Outside of this dedication: (1) Partners are able to engage digitally through social media that has already been created, in this case by Dai NU and LDNU managers; (2) Partners are capable of managing accounts of engagement well to continue to grow; (3) Partners are able to make videos of engagement; (4) Partners can read books of Nasoibh Ibad as reference material for engaging in engagement; (4) Publication of articles in accredited national journals; (5) Publication of articles on national seminars resulting from dedication to the community organized by the University of Nurul Huda; (6) Formation of mutually beneficial cooperation between the University of Noorl Huda OKU East with the community and the Doi NU in the environment of LDNu OKU Eastern